MOTIVASI, PERMASALAHAN DAN ALTERNATIF SOLUSI PROGRAM SISKA (SISTEM INTEGRASI SAPI DAN KELAPA SAWIT) DI KABUPATEN PASAMAN BARAT - Bagus Dimas Setiawan; Arfa’i Arfa’i; Yuliaty Shafan Nur (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
This activity aims to see a. The potential of existing natural resources; b. Breeders' interests and behaviour and c. Knowing the problems and alternative solutions that can be done for the development program of the SISKA (cattle-oil integration system) in West Pasaman Regency, West Sumatra. The monitoring method is carried out using a survey of group member farmers. Monitoring results show that West Pasaman Regency has the potential to provide animal feed ingredients from palm oil plants. The form of feed ingredients is palm fronds, palm mud, and palm kernel meal. Especially in the SISKA development centre area, namely Sub district: Luhak Nan Duo, Sasak Ranah Pasisie, Pasaman, and Kinali. Farmer group members have a high motivation in running a business. Problems with the implementation of the SISKA program have not yet run optimally. The proof is, although cow's livestock waste has been used as compost, but palm oil waste as feed is only used in some groups. Then the level of knowledge and skills of farmers is still relatively low. Local government supervision facilities are still lacking. Therefore, appropriate policies and collaboration are needed to accelerate SISKA's development efforts in the future.